Implementasi Fatwa DSN-MUI Tentang Murabahah pada Pembiayaan Dana Kredit Usaha Rakyat (KUR) di Bank BRI Syariah KCP Parung-Bogor - Khaeruddin, Khaeruddin; Hidayatullah, Syarif; Astiwara, Endy Muhammad (Tasyri' : Journal of Islamic Law, 2024)
This research aims to determine the procedures for financing KUR funds and determine the implementation of the DSN-MUI Fatwa regarding Murābaḥah in financing KUR funds and legal issues regarding its implementation at Bank BRI Syariah KCP Parung-Bogor. This research uses qualitative research. The data that supports this study comes from primary sources in the form of interviews with respondents and secondary material using a juridical-empirical approach. Based on the research that has been conducted, it can be concluded that sharia-based banking has been able to implement and realize its existence as a sharia financial institution (LKS) which adheres firmly to Islamic sharia law, especially in the practice of muamalah which has been determined by the Indonesian Ulema Council through its institution, namely the National Sharia Council